Isolated trisomy 11 in de novo acute myeloid leukemia - Krum,Everson A. (2008)
The real mechanism involved in trisomies and leukemogenesis remains unknown and more information about this connection is essential, but unfortunately the clinical outcome and hematological profile of patients with isolated trisomy 11 and AML have not been well characterized. Considering the limited data on the specific disease entity, the current report describes two cases of de novo acute monocytic leukemia (AMoL) and isolated +11, in which this event was further characterized.